Development of Some Antiplatelet Salts as Drug Active Ingredients and Investigation Biological Activities - Uslu, Harun; Satilmis, Basri; Uyumlu, Ayse Burcin; Saglik, Begum Nurpelin; Levent, Serkan; Ozkay, Yusuf; Benkli, Kadriye (Springer, 2023)
In this study, prasugrel and prasugrel salts: prasugrel + trans-1,2-cyclohexanedicarboxylic acid (1a), prasugrel + maleic acid (2a), prasugrel + citric acid (3a), prasugrel + oxalic acid (4a), and prasugrel + trometamol (5a) were synthesized and investigated for their biological activities.Ex vivo antiplatelet and in vitro cytotoxic activities were experimentally researched. Antiproliferative activity was not observed for prasugrel and prasugrel salts, and it was also determined that there was no cytotoxic effect. Ex vivo experiments were carried out on diabetic and nondiabetic rats. When the study results were examined, 2a and 3a were seen to be effective prasugrel salts for antiplatelet activity.
Keywords: Prasugrel; Prasugrel salts; antiplatelet; cytotoxic; diabetes